The Effects of Heat Stress on Physiological Parameters and Oxidative Stress Markers in Healthy Adults in Almuthana, Iraq - Hassan, Noora A. (American Journal of Biology and Natural Sciences, 2025)
Background: Almuthana Province in southern Iraq experiences extreme ambient temperatures exceeding 50°C during the summer months, leading to severe heat stress for the local population. There is a lack of research on physiological and biochemical responses to extreme heat exposure in the region. Objective: To examine the effects of acute heat stress on physiological parameters and oxidative stress biomarkers in healthy adults living in Almuthana, Iraq. Methods: We conducted a cross-sectional study of 120 healthy adults (60 males, 60 females, 20-45 years) under extreme summer months (July-August 2024). We exposed participants to controlled heat exposure (45°C, 30% relative humidity) for 60 minutes. We collected physiological parameters, including core body temperature, heart rate, blood pressure, and sweat rate. We collected blood to determine oxidative stress biomarkers including malondialdehyde (MDA), superoxide dismutase (SOD), catalase and reduced glutathione (GSH). Results: The results showed a significant change in core body temperature (38.9±0.4°C vs. 36.8±0.3°C, p<0.001), heart rate (118±12 bpm vs. 72±8 bpm, p<0.001), and systolic blood pressure (142±15 mmHg vs. 118±10 mmHg, p<0.001) following heat exposure. MDA increased by 68% (p<0.001) and markers of antioxidant activity, SOD decreased by 23% (p<0.001), catalase decreased by 31% (p<0.001), and GSH decreased by 28% (p<0.001). Additionally, males had larger physiological stress responses than females. Conclusion: Acute heat stress results in pronounced impairments to physiological homeostasis in healthy adults of Almuthana, Iraq, and induces oxidative stress to the biological system. The conclusions of this study could benefit occupational health and safety measures in populations that work or live in extreme heat conditions.